Impact Assessment of Cassava YTP 2 Cultivation in Tamil Nadu - T. Rajendran (MultiTech Publisher, 2023)
Cassava is being one of the essential crop cultivated in Tamil Nadu, this study was attempted to estimate the impact assessment and to examine the efficiency of different marketing channels. Tamil Nadu formed the universe of the study. Salem district was purposively selected since area wise it stood first in tapioca cultivation among different districts of Tamil Nadu. Multi-stage random sampling pertains to the selection of the blocks followed by villages. Thalivasal and Macheri block was selected in Salem district. Three villages from Thalivasal block namely Kamakapalayam, Sitheri and Thiyaganur; Three villages from Macheri block namely Vellar, Pukkampatti and Olaipatti was selected purposively. From each village 15 cassava growers. This will constitute 90 cassava growers were selected randomly. Apart from this, primary data was collected from 10 sago industries, 20 sago wholesaler, 20 tuber wholesaler, 20 value addition processor and 30 retailers. The reference year for the study was the agriculture year 2021-22. The result revealed that cultivation of Cassava YTP 2 is a profitable venture. But as far as marketing is considered, the bulkiness and perishability of Cassava YTP 2 limits the bargaining power of farmers. Market intermediaries assume a dominating role ultimately reducing the farmer’s share on consumer rupee. The study suggests that the farmers may be encouraged to form region based Tapioca Farmers Association or Co-operative marketing Society through which marketing of Cassava YTP 2 may be routed through, so as to establish a collective bargaining mechanism. This system could also restrict the role of unnecessary market intermediaries.